2019
DOI: 10.1007/s10984-019-09281-2
|View full text |Cite
|
Sign up to set email alerts
|

The flipped classroom: supporting a diverse group of students in their learning

Abstract: Higher education faces several challenges including both increased student diversity and the use of technologies. The flipped classroom approach has been proposed as a way to address some of these challenges. This study examined the effects of a flipped classroom trial conducted during a Master's course at the Vrije Universiteit Amsterdam in the Netherlands. Half of the course was taught in a traditional lecture style while the remaining half was replaced by flipped classrooms. Interviews and focus-group discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
74
1
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(91 citation statements)
references
References 30 publications
6
74
1
10
Order By: Relevance
“…The most amount of positive effect was observed on visual style and the least amount of positive effect was observed on kinesthetic style. The results of this part can provide empirical evidence in response to Goedhart et al. (2019) quest for further investigation as to why not all students agreed that the FL approach contributed to positive learning outcomes.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The most amount of positive effect was observed on visual style and the least amount of positive effect was observed on kinesthetic style. The results of this part can provide empirical evidence in response to Goedhart et al. (2019) quest for further investigation as to why not all students agreed that the FL approach contributed to positive learning outcomes.…”
Section: Discussionmentioning
confidence: 95%
“…(2018), including extra workload for learners and teachers, the technology/internet related problems, and writing anxiety. Moreover, as these studies mainly concentrated on the efficacy of the FL approach compared to the traditional methods, they ignored psychological factors like motivation, personality traits, and learning styles in flipped learning environments (Goedhart et al., 2019; Kim, 2017). Therefore, lack in the literature is a study that considers students’ learning styles in relation to the FL strategy, as there is a widespread belief, especially among practitioners that tailoring teaching to the students’ learning styles would enhance learning outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The reserved in-class time may be utilized for teamwork, comprehension tasks, in-depth analysis and discussions, collaborative or individual assignments etc. It provides students with more opportunities for interaction, developing their critical thinking, analysis and problem solving skills [4].…”
Section: Optimization Of the In-class Timementioning
confidence: 99%
“…One group embraces the new model, while the other defends a more traditional methodology. In their study of a flipped classroom project, Goedhart, Blignaut-van, Moser, & Zweekhorst (2019) recount that, while the experience overall was a positive one, not all the students agreed that the FC had contributed to improving their learning results. Elsewhere, Strayer (2012) found that students who had completed a class using a FC model were unsatisfied with the way the class's structure had served to guide them through their learning tasks.…”
Section: Introductionmentioning
confidence: 99%
“…When the flipped classroom is met with such negative reactions, it might be due to the characteristics of the students themselves. For example, they might not have the academic experience or the scientific reasoning and autonomous learning required of them in a flipped classroom (Jensen, Holt, Sowards, Ogden, & West, 2018;Goedhart et al, 2019). Some studies have also suggested that the implementation of this model might be hindered because of resistance to the necessary changes in both students' and teachers' roles.…”
Section: Introductionmentioning
confidence: 99%